U-Th dating of Lake Lisan (late Pleistocene Dead Sea) aragonite and implications for glacial East Mediterranean climate change - Schramm, Alexandra; Haase, Alexandra; et al. (Geochimica Et Cosmochimica Acta, 2004)
The U-Th ages provide a context to unravel the limnological history of Lake Lisan. Boundaries between the Lower, Middle, and Upper stratigraphic units correspond to the MIS 4/3 and 3/2 transitions, respectively. During MIS 2 and 4 the lake generally showed a stable two-layer configuration and a positive fresh-water balance, reflected by deposition of laminated aragonite-detritus. Dry intervals during MIS 2 and 4 are indicated by thick gypsum layers and an inferred depositional hiatus, which are temporally associated with Heinrich events HI at similar to17 ka and H6 at similar to65 ka, respectively. During MIS 3 the lake level was unstable with intermittent dry periods indicated by abundant clastic layers and a significant hiatus between similar to43-49 ka. Clastic layers are associated with Dansgaard-Oeschger events during MIS 3, and indicate lake level declines during abrupt Northern Hemisphere warmings. Overall, the climate of the Eastern Mediterranean region shows a strong linkage to the Northern Hemisphere climate, with increasing lake size and stability during cold periods, and fluctuations and dessication during warmings and Heinrich events. Copyright (C) 2004 Elsevier Ltd.